Criminal Liability in the Crime of Theft with Benefit-Based Aggravation (Case Study of Criminal Case Decision No. 666/Pid.B/2024/ Pn Mks) - Mevifah De Nanda Aurelia; Umar Ma’ruf (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The crime of aggravated theft, as stipulated in Article 363 of the Criminal Code (KUHP), constitutes a violation of human rights, particularly the right to property. This study aims to determine and analyze the criminal liability for aggravated theft based on expediency and the weaknesses of criminal liability for perpetrators of aggravated theft based on expediency, as outlined in Criminal Case Decision No. 666/Pid.B/2024/Pn Mks, as well as the formulation of the crime of aggravated theft based on expediency. This research method uses a socio-legal (juridical-sociological) approach. The research specification used is descriptive analysis. In this study, the types of data used are divided into two main categories: primary data and secondary data. Data collection methods in this study were conducted by combining normative and empirical approaches, namely through literature studies, field observations, and in-depth interviews. The problem is analyzed using the Theory of Criminal Responsibility, Theory of Legal Systems and Theory of Legal Utilities. The results of the study indicate that the criminal liability of the perpetrator of the crime of aggravated theft based on expediency in Decision Number 666/Pid.B/2024/PN Mks indicates that the judge assessed that all elements of the crime stipulated in Article 363 of the Criminal Code, both objective and subjective, were fulfilled, so that the defendant was legally and convincingly proven guilty. Weaknesses in the application of criminal liability based on expediency in this case include the lack of adequate consideration of the defendant's social, psychological, and economic aspects, as well as the lack of consideration of the defendant's social, psychological, and economic aspects. The formulation of the crime of aggravated theft based on expediency should integrate preventive, repressive, and restorative approaches in a balanced manner, so that the objectives of punishment can be achieved comprehensively.